PENERAPAN MANAJEMEN PEMASARAN BERBASIS DIGITAL MARKETPLACE UNTUK MEMPERLUAS JANGKAUAN PASAR UMKM DI PAUH, KOTA PADANG - Wahyudi, Harry; Malik, David; Adha, Howardi Visza; Amrullah, Amrullah; Suandi, Edi; Suhanda, Mya Yuwanita (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the local economy in Pauh District, Padang City. However, most MSMEs still face obstacles in expanding their market reach due to limited effective marketing strategies. Marketing activities are still dominated by conventional methods, resulting in suboptimal utilization of digital technology, particularly digital marketplaces. This situation results in low product competitiveness and limited market access. This community service program aims to implement digital marketplace-based marketing management to expand the market reach of MSMEs. The focus of the activity is to increase the capacity of business actors in understanding and managing digital marketing through marketplace platforms. The main challenges faced by partners include low digital literacy, limited skills in managing online stores, and a limited understanding of integrated digital marketing strategies. The implementation method is participatory and applied through the stages of needs identification, digital marketing management training, mentoring in creating and managing marketplace accounts, and monitoring and evaluation. Materials cover digital marketing concepts, product and content management, promotional strategies, and online customer service. The expected results are improved MSME skills in utilizing marketplaces, the establishment of active online stores, and the expansion of market reach and sustainable sales potential